Fair-faced concrete and application thereof

By adjusting the slurry and bone ratio, increasing the double use of ore powder and fly ash, and adding microsilicon powder and barium chloride, the ammonia gas generation and foaming problems caused by fly ash in concrete are solved, and the appearance and durability of concrete are improved.

CN119797841APending Publication Date: 2025-04-11YICHANG ZHENGXIN CONSTR ENG TESTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991050.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When fly ash is used in concrete, due to the presence of alkaline conditions and heat, the ammonium salt decomposes and reacts with alkaline cement, releasing ammonia, causing the concrete to foam, affecting its appearance, strength and durability.

Method used

By adjusting the slurry and bone ratio, increasing the double doping of ore powder and fly ash, and adding microsilicon powder as an alkaline exciter, the fly ash hydration reaction process is accelerated, and barium chloride is used to reduce ammonia gas generation.

Benefits of technology

It effectively improves the appearance quality of concrete, controls the gas content, improves the stability and durability of concrete, and avoids foaming problems caused by ammonia gas generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797841A_ABST
    Figure CN119797841A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses fair-faced concrete and application thereof. The concrete per cubic meter is prepared from the following raw materials: 120 to 165 Kg of water, 120 to 160 Kg of cement, 80 to 100 Kg of mineral powder, 60 to 100 Kg of fly ash, 608 to 838 Kg of fine aggregate and 1288 to 1418 Kg of coarse aggregate, the admixture comprises a water reducing agent, an air entraining agent, a defoaming agent, an alkali activator silica fume and barium chloride. The invention provides fair-faced concrete and application thereof, and the prepared fair-faced concrete reaches C30W6F100 level, and can be used for an upper wall body of a main power house of a hydropower station dam, a water inlet gate pier and a breast wall, a tail water gate pier and a flow channel, a flow channel bottom plate and a pier wall, an upstream retention wall and an end wall and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a kind of plain concrete and application thereof. Background Art

[0002] Fair-faced concrete technology was introduced to China in the 1970s. In the early days, it was mainly used in concrete prefabricated exterior wall panels, bridges, municipal engineering and other parts. With years of research by engineering and technical personnel, the application scope of fair-faced concrete has been rapidly developed. Fair-faced concrete is beautiful and generous, and its advantages of one-time molding without secondary decoration are sought after by a large number of engineering and technical personnel.

[0003] Fly ash is the main solid waste discharged by coal-fired power plants. Adding fly ash to concrete can replace part of cement, reduce water consumption, improve the workability of concrete mixture, and enhance concrete impermeability. With the promotion and application of ammonia desulfurization and denitrification technology in coal-fired power plants, a large amount of ammonia nitrogen by-products remain in fly ash. When fly ash is used in the concrete mixing process, due to the presence of alkaline conditions and a large amount of heat, the ammonium salt in the fly ash decomposes and reacts with alkaline cement to release ammonia gas, causing concrete foaming, which not only affects its appearance, but also has an adverse effect on the strength and durability of concrete. Summary of the invention

[0004] The invention provides a kind of fair-faced concrete and application thereof. The prepared fair-faced concrete reaches the C30W6F100 level and can be used for the upper wall of the main powerhouse of a hydropower station dam, the water inlet pier and breast wall, the tailwater pier and flow channel, the flow channel bottom plate and pier wall, the upstream retaining wall and end wall, etc.

[0005] The technical solution of the present invention is to provide a kind of concrete which includes the following raw materials per cubic meter: 120-165 kg of water, 120-160 kg of cement, 60-100 kg of fly ash, 80-100 kg of mineral powder, 608-838 kg of fine aggregate, and 1288-1418 kg of coarse aggregate; and also contains admixtures, which include water reducing agent, air entraining agent, defoaming agent, alkaline activator and barium chloride.

[0006] Optionally, the water reducer is a polycarboxylate water reducer, and the dosage thereof is 0.5% to 0.8% of the dosage of the cementitious material; the dosage of the air entraining agent is 0.001 to 0.06% of the dosage of the cementitious material.

[0007] Optionally, the defoaming agent is a polyether defoaming agent, and the dosage is 0.003% to 0.05% of the amount of the gelling material.

[0008] Optionally, the alkaline activator is microsilica powder, and the added amount is 2% to 4% of the total amount of the cementitious material.

[0009] Optionally, the amount of barium chloride added is 0.3% to 1% of the amount of the gelling material.

[0010] Optionally, the water-cement ratio in the concrete is ≤0.45, the sand ratio is ≤44%, and the air content of the concrete is controlled at 2.5%-3.5%.

[0011] Optionally, the concrete is one-graded, two-graded or three-graded concrete; the coarse aggregate is small stone with a particle size of 5-20 mm, medium stone with a particle size of 20-40 mm and large stone with a particle size of 40-80 mm; in the first-grade concrete, the coarse aggregate is small stone; in the second-grade concrete, the coarse aggregate is small stone and medium stone; in the third-grade concrete, the coarse aggregate is small stone, medium stone and large stone.

[0012] Optionally, the void ratio of the coarse aggregates after combination measured by the close packing density test method is ≤38%.

[0013] The invention also relates to the application of the plain concrete in a hydropower station dam project.

[0014] The present invention has the following beneficial effects: Conventional plain concrete has complex construction technology, high precision in the control of raw materials and mix ratios, and high reliance on material quality. Formwork and demoulding material costs are high (most of them use Finnish Visa panels). In order to make full use of on-site floor materials and take into account the impact of construction period and cost, the optimal effect can be achieved by improving concrete performance while meeting appearance requirements.

[0015] Based on sufficient experimental research, the present invention finds that adjusting the mortar-to-bone ratio has a great influence on the production of bubbles in concrete. The pure cementitious material slurry generally does not produce bubbles, but there are more bubbles in the appearance of the mortar. This is mainly because the coarse and fine aggregates themselves contain void volume, and the cementitious material slurry cannot fully fill its voids during the concrete mixing process. In addition, during the concrete mixing process, the angular surfaces of the coarse and fine aggregates pierce the thin film formed by the cementitious material slurry, which will also introduce external bubbles. Therefore, increasing the mortar-to-bone ratio is helpful to improve the appearance of concrete. This ratio requires the absolute volume of the slurry to be above 0.32.

[0016] The air content of concrete also has a great influence on the generation of bubbles. During the research process, the method of first eliminating and then introducing was adopted. On the one hand, polyether defoaming agents were used to eliminate harmful bubbles in concrete, and on the other hand, air-entraining agents were used to introduce bubbles below 300μm to enhance the stability of cementitious material slurry. The study found that the stability of concrete is best when the air content of concrete is between 2.5% and 3.5%. The low air content will not cause segregation to affect the appearance of the concrete, nor will the loss of air content cause stability fluctuations.

[0017] The present invention adopts the dual blending of mineral powder and fly ash, adds microsilica powder as an alkaline activator to consume a part of hydroxide to accelerate the process of fly ash hydration reaction, and uses a certain amount of barium chloride to further reduce the generation of ammonia. These measures complement each other and are indispensable. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a graph showing the relationship between the sand ratio and concrete bubbles in 3.1 of the present invention; Figure 2 This is a photo of QSP-X-01 in 3.1 of the present invention after being vibrated for 45 seconds but before demoulding; Figure 3 These are pictures of concrete prepared in Examples 1 to 4 of the present invention; Figure 4 These are pictures of the concrete pouring vibration process of Example 1 and Example 4, with the vibration durations being 0s, 8s, 30s and 60s respectively.

[0019] Figure 5 The following are the effects of demoulding the mix concrete of Example 1 using different demoulding materials. DETAILED DESCRIPTION

[0020] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.

[0021] The plain concrete to be prepared in the present invention meets the grade requirement of C30W6F100.

[0022] 1. Raw materials The experimental cements used in the following examples are P•O42.5 ordinary silicate and P•LH42.5 low-heat silicate cement, wherein all indicators of P•O42.5 ordinary silicate meet the requirements of the "General Portland Cement" (GB175-2007) standard, and all indicators of P•LH42.5 low-heat silicate cement meet the requirements of the "Medium Heat Portland Cement, Low Heat Portland Cement" (GB / T200-2017) standard. The following examples are illustrated by using P•O42.5 ordinary silicate produced by Esheng Cement Company and P•LH42.5 low-heat Portland cement produced by Jiahua Cement Plant of Sichuan Jiahua Co., Ltd., but the present invention is not limited thereto.

[0023] The fly ash is Class F II fly ash, and all indicators meet the requirements of the Technical Specification for Fly Ash Used in Hydraulic Concrete (DL / T 5055-2007). In the following examples, Class F II fly ash produced by Panan Power Plant of Guizhou Yueqian Electric Power Co., Ltd. is used, but the present invention is not limited thereto.

[0024] All indicators of fine aggregate meet the requirements of "Specifications for Construction of Hydraulic Concrete" (DL / T 5144-2015). The particle sizes of coarse aggregate are (5-20) mm small stone, (20-40) mm medium stone, and (40-80) mm large stone. All indicators meet the requirements of "Specifications for Construction of Hydraulic Concrete" (DL / T 5144-2015).

[0025] The water reducer adopts polycarboxylic acid high-performance water reducer, and all indicators meet the standard requirements of "Technical Specifications for Hydraulic Concrete Admixtures" (DL / T 5100-2014). The following examples use HLC-IX polycarboxylic acid high-performance water reducer (liquid) produced by Nanjing Ruidi High-tech Co., Ltd., but the present invention is not limited thereto. All indicators of the air entraining agent meet the standard requirements of "Technical Specifications for Hydraulic Concrete Admixtures" (DL / T 5100-2014). The following examples use HLC-AE613 concrete high-efficiency air entraining agent (liquid) produced by Nanjing Ruidi High-tech Co., Ltd., but the present invention is not limited thereto.

[0026] The water meets the standard requirements for water for concrete mixing in the "Specifications for Hydraulic Concrete Construction" (DL / T 5144-2015).

[0027] The raw materials of concrete used in the above tests meet the standard requirements for concrete materials in the "Specifications for Hydraulic Concrete Construction" (DL / T 5144-2015).

[0028] 2. Basic parameters of mix design 2.1 Water-cement ratio A larger water-cement ratio has a significant adverse effect on the appearance quality of concrete. The water in the concrete, excluding the part consumed in the hydration process, accounts for about 80% of the volume as free water. During the construction process, most of the free water can be discharged by vibration, and a small amount of water that cannot be discharged gathers to form bubbles under the action of vibration. It will eventually be extracted from the concrete in the form of evaporation, and large-diameter bubbles are easily formed on the surface of the concrete. For the plain concrete of the present invention, the water-cement ratio is controlled below 0.45.

[0029] 2.2 Aggregate gradation Since aggregate gradation has a significant correlation with the content and size of bubbles in concrete, poor gradation has a large void volume and is prone to produce bubbles with a diameter of more than 2 mm. The proportion of coarse aggregate can be measured according to the bulk density test method in the "Test Procedure for Sand and Gravel Aggregates for Hydraulic Concrete" (DL / T 5151-2014) to obtain the combination with the maximum compact density as the mixing ratio.

[0030] Table 1

[0031] The slump of normal concrete is controlled at 70mm-90mm, and the slump of pumped concrete is controlled at 180mm-200mm. The optimal mixture ratio is 55:45 (mass ratio) for the second-grade small stone: medium stone: large stone. The compact packing density of small stone: medium stone: large stone = 30:30:40 (mass ratio) is measured by using 15L volume liters for the third-grade small stone: medium stone: large stone, which is the optimal mixture ratio.

[0032] For plain concrete, the void ratio after the aggregates are combined should not be greater than 38%. According to the test results, the void ratios of the secondary and tertiary grades of artificial crushed stone coarse aggregates combined with coarse aggregates of different particle sizes in the optimal proportion after compaction are 36% and 37.1% respectively.

[0033] 2.3. Sand rate The use of a suitable sand ratio can increase the compactness of concrete and improve the workability and appearance quality of concrete. The optimal sand ratio of the present invention is preliminarily selected through a close packing density test, and the sand ratio is adjusted by a fixed water consumption. Several different sand ratios are preliminarily selected for trial mixing, and the sand ratio with good cohesion, water retention, sand content, stickiness and large slump is selected as the optimal sand ratio of the concrete mixture. When the water-cement ratio is 0.45, the optimal sand ratio of normal first-grade concrete is recommended to be 44%, the optimal sand ratio of normal second-grade and third-grade concrete is recommended to be 33% and 30% respectively, and the optimal sand ratio of pumped second-grade concrete is recommended to be 39%.

[0034] 3. Concrete appearance study The factors that affect the appearance of concrete are mainly bubbles and color difference. The appearance of concrete not only affects the aesthetics, but also the durability and structural safety of concrete.

[0035] The rising speed of bubbles is proportional to the size of the bubbles and inversely proportional to the viscosity of the slurry. Therefore, the smaller the viscosity, the easier it is for the bubbles to overflow. However, too low viscosity will cause the concrete to segregate and bleed, producing a large number of bubbles.

[0036] There is also a clear correlation between the air content and bubbles in concrete. The bubbles introduced by the air-entraining agent are relatively stable. However, adding the air-entraining agent to increase the uniformity and micro-bubbles will increase the viscosity of the concrete and increase the resistance to the bubbles overflowing.

[0037] The bubbles introduced by the water reducer are small and unstable, which has a great impact on the concrete surface. Therefore, when compounding the water reducer, a certain amount of defoamer needs to be added to eliminate the unstable bubbles in the water reducer.

[0038] When the ammonium ion content in fly ash exceeds the limit value, it is easy to produce ammonia when it meets alkaline cement. This kind of chemical reaction occurs continuously during the concrete hardening process, which not only affects the appearance but also has an adverse effect on the strength of the concrete.

[0039] The following discusses the impact on concrete appearance from several dimensions: sand ratio, air content, slump, paste volume, defoamer type and dosage.

[0040] In order to better observe the generation and discharge of bubbles during the construction of concrete mixtures, we customized a transparent acrylic test mold with a size of 300cm*300cm*450cm to observe the impact of the above parameter changes on the appearance of concrete.

[0041] 3.1 Effect of sand ratio on concrete appearance Based on the normal secondary concrete mix ratio, the slump and air content of the concrete are guaranteed to be consistent, and the volume ratio of fine aggregate to paste is basically consistent. The effect of the change in sand ratio on the appearance is observed. The concrete mix ratio is shown in Table 2, and the statistics of concrete bubbles are shown in Table 3 (the area with the most dense bubbles on the facade of the test mold is selected, and bubbles below 2mm are taken as 2cm 2 The average number within the range, the number of bubbles 2-5mm and above 5mm are all counted.

[0042] Table 2

[0043] Table 3

[0044] With the increase of sand ratio, under the condition of consistent slump and air content, the bubbles in concrete have a significant growth trend. This may be because with the increase of sand ratio, the total specific surface area of ​​concrete aggregate increases, and the contact area with cementitious materials increases when the slurry volume remains unchanged. Mortar exceeding a reasonable range will increase the total porosity of concrete. Within a reasonable range, it will be easier to introduce air during mixing and vibration due to the increase in contact area, resulting in the bubbles in concrete always showing an increasing trend under the same construction process.

[0045] 3.2 Effect of air content on concrete appearance Based on the normal secondary concrete mix ratio, the slump of concrete is guaranteed to be consistent, the volume ratio of fine aggregate to paste is basically consistent, and the amount of air entraining agent is adjusted to make the air content of concrete change around 2%-6% to observe the effect of sand ratio change on appearance. The concrete mix ratio is shown in Table 4, and the statistics of concrete bubbles are shown in Table 5 (the area with the most dense bubbles on the facade of the test mold is selected, and bubbles below 2mm are taken as 2cm 2 The average number within the range, the number of bubbles 2-5mm and above 5mm are all counted.

[0046] Table 4

[0047] Table 5

[0048] As the air content decreases, the medium and large bubbles on the surface of concrete tend to increase significantly, which may be related to the reduced cohesion of concrete and the increased water bleeding rate; as the air content increases to a certain amount, a large number of uniform tiny bubbles begin to grow, the cohesion of concrete increases, and the tiny bubbles and medium-diameter bubbles tend to increase significantly, which may be related to the increased air resistance of concrete caused by the increased cohesion of concrete. According to the test results, the appearance quality is best when the air content is 2.5%-3.5%.

[0049] 3.3 Effect of fluidity on concrete appearance Ensure that the water-binder ratio of concrete is consistent, the gradation ratio of coarse aggregate is consistent, fine-tune the sand ratio and admixture dosage to gradually increase the fluidity of concrete, adjust the dosage of air-entraining agent to make the air content of concrete change around 2.5%-3.5%, and observe the changes in the appearance of concrete. The concrete mix ratio is shown in Table 6, and the statistics of concrete bubbles are shown in Table 7 (select the area with the most dense bubbles on the facade of the test mold, and take 2cm for bubbles below 2mm 2 The average number within the range, the number of bubbles 2-5mm and above 5mm are all counted.

[0050] Table 6

[0051] Table 7

[0052] With the increase of concrete fluidity, all levels of bubbles on the concrete surface show a significant downward trend, which may be related to the reduction of concrete cohesion and concrete air exhaust resistance. From the test results, the concrete has good workability. Under the condition of low water bleeding rate, with the increase of fluidity, the bubbles on the concrete surface have been showing a downward trend.

[0053] 3.4 Effect of paste volume on concrete appearance Ensure that the water-cement ratio of concrete is consistent, the gradation of coarse aggregate and the sand ratio are consistent, fine-tune the dosage of admixtures to ensure the consistency of concrete fluidity, adjust the unit water consumption (paste-aggregate ratio) to observe the changes in the appearance of concrete, the concrete mix ratio is shown in Table 8, and the statistics of concrete bubbles are shown in Table 9 (select the area with the most dense bubbles on the facade of the test mold, and take 2cm for bubbles below 2mm 2 The average number within the range, the number of bubbles 2-5mm and above 5mm are all counted.

[0054] Table 8

[0055] Table 9

[0056] 3.5 Effect of defoamer on concrete appearance Ensure that the concrete mix ratio is consistent, adjust the type and dosage of the defoamer and observe the changes in the appearance of the concrete. The concrete mix ratio is shown in Table 10, and the statistics of concrete bubbles are shown in Table 11 (select the area with the most dense bubbles on the facade of the test mold, and take 2cm for bubbles below 2mm). 2 The average number within the range, the number of bubbles 2-5mm and above 5mm are all counted.

[0057] Table 10

[0058] Table 11

[0059] Defoaming agent can significantly eliminate harmful bubbles in polycarboxylic acid water-reducing agent and concrete mixing process. Polyether defoaming agent is slightly better than silicone defoaming agent, but it also has a more obvious effect on the tiny beneficial bubbles introduced by air-entraining agent. To maintain a certain air content in the concrete production process, it is necessary to increase the amount of air-entraining agent.

[0060] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0061] The mix ratios of Example 1 to Example 4 are shown in Table 12 below.

[0062] Table 12

[0063] The concrete prepared in Examples 1 to 4 was prepared by first mixing the aggregates, then adding the cementitious materials and other admixtures in sequence, and finally adding the barium chloride to mix evenly. The total stirring time was 2 minutes, and finally adding the mixture into the mold to form the concrete. The photos after forming are shown in FIG. Figure 3 It can be seen that from Example 1 to Example 4, the number and size of the holes in the concrete block are getting smaller and smaller, and the appearance quality is getting better and better.

[0064] The concrete of Example 1 to Example 4 was tested according to DL / T5150-2017 (Test Procedure for Hydraulic Concrete), and the specific performance indicators are shown in Table 13 below.

[0065] Table 13

[0066] It can be seen from the table above that the concrete in Example 4 is significantly better than the other examples. In addition, when preparing the concrete in Example 1 and Example 4, after mixing, the concrete is placed in an acrylic mold for vibration molding, with a vibration frequency of 50 Hz ± 3.3 Hz and a time of 60 seconds. The specific comparison photos are shown in the following figure. Figure 4 During the vibration process, most of the bubbles on the surface of the conventional concrete in Example 1 have been discharged after 8S of vibration. At this time, the concrete is in an unstable state due to the internal gas content, and the slurry is easy to segregate. The surface is easy to delaminate and the solid particles of the cementitious material are concentrated, and the subsequent exhaust speed is significantly slowed down. New bubbles are constantly generated inside the concrete during 8-30S. After 30S, the bubbles inside the concrete are reduced. At this time, the ammonia released after the reaction of fly ash and cement is mainly released, and tiny bubbles are continuously generated. Vibration has basically failed to produce any effect; in Example 4, there are no obvious bubbles on the surface of the concrete after vibrating for about 8S. Because the slurry volume is large, few external bubbles are introduced during the mixing process, and the air content inside the concrete is stable. At this time, the anti-segregation ability is strong, the concrete is quickly exhausted, and almost no large bubbles are generated inside. After 8S, the tiny bubbles generated inside the concrete are few, and there is almost no phenomenon on the surface, and there is no phenomenon of bubble aggregation to generate large bubbles. After 30S of vibration, the concrete surface is smooth and there are no obvious traces of bubbles.

[0067] Based on the mix ratio of Example 1, when preparing concrete, the aggregates are first mixed, then the cementitious materials and other admixtures are added in sequence, and finally the barium chloride is added and mixed. The total stirring time is 2 minutes. When forming, template cloth, water-based mold release agent, oily mold release agent with defoaming component, and edible oil are used respectively. A 450*450*450 steel test mold is used on site, and a Φ50 hose is used to vibrate for 20 seconds. The effect after demoulding is as follows Figure 5 In the figure, 5-1 is the template cloth, 5-2 is the water-based release agent, 5-3 is the oil-based release agent with defoaming components, and 5-4 is edible oil. From the effect after demoulding, the template cloth has the best defoaming effect, but some concrete forms a rough surface after slurrying. The water-based release agent is basically equivalent to the oil-based release agent with defoaming components, and the edible oil has the worst effect.

[0068] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A kind of plain concrete, characterized in that: Each cubic meter of concrete includes the following raw materials: 120-165 kg of water, 120-160 kg of cement, 80-100 kg of mineral powder, 60-100 kg of fly ash, 608-838 kg of fine aggregate, and 1288-1418 kg of coarse aggregate; it also contains admixtures, which include water reducing agent, air entraining agent, defoaming agent, alkaline activator and barium chloride.

2. The plain concrete according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer, and the dosage thereof is 0.5% to 0.8% of the dosage of the cementitious material; the dosage of the air entraining agent is 0.001% to 0.06% of the dosage of the cementitious material.

3. The plain concrete according to claim 1, characterized in that: The defoamer is a polyether defoamer, and the dosage is 0.003% to 0.05% of the amount of the gelling material.

4. The plain concrete according to claim 1, characterized in that: The alkaline activator is microsilica powder, and the added amount is 2% to 4% of the total amount of the cementitious material.

5. The plain concrete according to claim 1, characterized in that: The amount of barium chloride added is 0.3% to 1% of the amount of the cementitious material used.

6. The plain concrete according to any one of claims 1 to 5, characterized in that: The water-cement ratio of the concrete is ≤0.45, the sand ratio is ≤44%, and the air content of the concrete is controlled at 2.5%-3.5%.

7. The plain concrete according to any one of claims 1 to 5, characterized in that: The concrete is one-graded, two-graded or three-graded concrete; the coarse aggregate is small stone with a particle size of 5-20 mm, medium stone with a particle size of 20-40 mm and large stone with a particle size of 40-80 mm; in the first-grade concrete, the coarse aggregate is small stone; in the second-grade concrete, the coarse aggregate is small stone and medium stone; in the third-grade concrete, the coarse aggregate is small stone, medium stone and large stone.

8. The plain concrete according to claim 7, characterized in that: After the coarse aggregate is combined, the void ratio measured by the tight packing density test method is ≤38%.

9. The plain concrete according to claim 7, characterized in that: First mix the aggregates, then add the cementitious material and other admixtures in turn, and finally add the barium chloride and mix well.

10. Use of the plain concrete according to any one of claims 1 to 9 in a hydropower station dam project.